Conceptualizing and investigating organizational politics: A systematic review of the literature - Doldor, Elena (Cranfield University, 2007)
In the last decades, there has been a growing academic interest for the concept of organizational politics. Although this body of literature is expanding, the research remains fragmented in terms of theoretical and methodological approaches, and several conceptual ambiguities persist despite the accumulation of empirical data. Using a systematic review methodology, this paper analyses the existent literature in the field of organizational politics by exploring two main sources of information: journal articles and books. The process of searching and assessing the literature is described in detail and the decisions made with respect to the inclusion/exclusion of the sources are accounted for at every stage. Overall, fifty one journal articles and seven books were systematically reviewed. In the conceptual analysis of the core sources, the focus was on the way the concept of organizational politics is conceptualized and investigated in the existent literature. In a first part, the strengths and the shortfalls of various theoretical frameworks are discussed, in an attempt of conceptual integration. The findings are organized around three umbrella-concepts: organizational politics, political behaviours and political skill. In a second part, the research methods used in this field are carefully examined. Qualitative approaches were found to be less frequent than quantitative ones. Moreover, these last ones have been grouped into a methodological taxonomy. This in-depth analysis of the literature points out the implications that methodological choices have for the conceptual clarity of the field. Finally, several limitations of this systematic literature review are acknowledged. Opportunities for future research in the field of organizational politics are discussed, as related to the progress of the doctoral project.